Pengaruh Kompetensi Guru, Pelayanan Dan Brand Image Terhadap Keputusan Orang Tua Menyekolahkan Anak Pada SMAK Seminari Agats, Asmat, Papua Selatan - Wahyu Indriyani; Fathorrahman; Theresia Pradiani (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2023)
Teacher competence and maximum service are keys to the success of education. The maximum of teachers in developing the skills and limitations of the support literature in the learning process will affect the education and the brand of a school. The purpose of this study is to know the influence of teacher competence service and brand image, on a parent’s decision to send a student to school in SMAK Asmat Agats Seminary. The data used in the study are primary data divided from the distribution of questionnaires. This research data with sampling conducted using a sample with a total of 50 people. Research data is quantitatively treated description using technical retention and tested try using spss the study concluded that (1) teacher competence has a significant impact on the choice to send children to school, (2) service has a significant impact on the options education of children, (3) the brand image has a significant impact on the choice of children education